Subsidiary divestiture and acquisition in a financial crisis: Operational focus, financial constraints, and ownership - Zhou, Yue Maggie; Li, Xiaoyang; Svejnar, Jan (Journal of Corporate Finance, 2011)
We exploit parent- and subsidiary-level data for publicly listed firms in Thailand before, during, and after the 1997 Asian Financial Crisis to investigate the extent to which firms with different types of ownership restructure their business portfolios, in terms of divestitures and acquisitions. We compare restructuring choices made by firms mostly owned by (a) domestic individuals with block shares (family firms), (b) domestic firms and/or institutions (DI firms), and (c) foreign investors (foreign firms). We show that following the crisis (1) foreign firms' restructuring behavior is the least affected; (2) domestic firms owned by families and domestic institutions (DI) behave similarly to one another; (3) domestic firms do not increase divestiture in their peripheral segments to improve operational focus or to obtain cash in a credit crunch; they actually reduce divestiture in core segments; and (4) domestic firms also significantly reduce the acquisition of new subsidiaries. Our results challenge traditional explanations for divestiture such as corporate governance, operational refocus, and financial constraints. They indicate that in the great uncertainty of a crisis, domestic firms are able to hold onto their core assets to avoid fire-sale. In essence, they act more conservatively in churning their business portfolios.